Chenopodium murale leaf extract, a potent virus inhibitor - H.N. VERMA, NEETA SRIVASTAVA and (Indian Phytopathology, 2002)
The aqueous extract of fresh leaves of Chenopodium murale showed antiviral activity and induced systemic resistance in the plants reacting hypersensitively to tobacco mosaic virus and sunnhemp rosette virus. The inhibitor in the leaf extract was active even when heated to 98Â°C for 10 min, diluted upto 1:20 and stored upto 8 days at 4Â°C. The inhibitor was non-dialyzable, and precipitated by 60% ammonium sulphate.